PENERAPAN MODEL PROBLEM BASED LEARNING MENGGUNAKAN METODE BERNYANYI UNTUK MENINGKATKAN HASIL BELAJAR IPA PESERTA DIDIK KELAS IV SDN 41 KURANJI - Elsa Viora Elsa Viora; Dini Maielfi; Trinda Farhan Satria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low science learning outcomes of grade IV students of SDN 41 Kuranji. Where in the learning process students quickly forget the subject matter that has been delivered by the teacher, this can be seen when the teacher repeats the lesson and the students cannot answer it, there are passive listener students, even some students are sleepy during the learning process, and some students pay less attention to the teacher when explaining the learning material. In addition, the implementation of learning activities is still centered on the teacher. This study aims to describe the improvement of science learning outcomes through the application of the Problem Based Learning model using the singing method in grade IV of SDN 41 Kuranji. The approach used in this study is quantitative and qualitative. The type of research that the researcher conducted was classroom action research. The study was conducted in 2 cycles with 3 meetings. The object of this study was grade IV students of SDN 41 Kuranji. The data collection techniques used were observation, learning outcome tests and documentation. The assessment instruments used in this study were observation sheets, test questions, documentation and data analysis. The average percentage of learning outcome completion obtained in the cycle I test was 66,66% and increased in cycle II to 85,19%.